Same cheat, different wrapping: DRG scandals and accountability in Germany and Norway - Neby, S; Lægreid, P; Mattei, P; Mitra, MAHIMA (Stein Rokkan Centre for Social Studies, 2013)
Across the world, the DRG system is used for administrative and financial purposes in hospitals. Combining statistical registration and aggregation of data on medical activity with activity based financing; DRGs have proven to be a powerful, incentive‐based performance management system with large implications for the wider governance of hospitals. Although economic dysfunctions of DRGs are widely reported within health economics, the organizational basis of the system and its implications for governance is less explored. This working paper aims to show how DRGs create negative side effects in both the Norwegian and the German hospital system. It is argued that although the adverse effects of the DRG system are comparable across country, the ways in which such effects are handled differs considerably between the two systems. We investigate a set of eight scandals or cases that have been dealt with quite differently in Norway and Germany, showing how accountability relationships and processes take different shapes and play different roles in the two countries. A lesson to draw is that accountability is not an easy fix or a ready‐made solution for handling adverse effects, but that the likely outcome is ambiguity and complexity defined by reform trajectories, institutional dynamics and the contextual factors of any given case.